Sexual practices, condom use and hiv testing among nursing undergraduates - Thelma Spindola; Vinícius Rodrigues Fernandes da Fonte; Elizabeth Rose Costa Martins; Márcio Tadeu Ribeiro Francisco; Carolina Passos Sodré; Claudia Silvia Rocha Oliveira (Universidade Federal de Santa Maria, 2017)
Aim: to identify sexual practices, condom use and the realization of diagnostic test for human immunodeficiency virus (HIV) infection among nursing students. Method: descriptive study with quantitative approach and sample for convenience. The scenario was two college institutions located in the city of Rio de Janeiro, Brazil. The participants were 250 nursing students. Data collection was performed with the help of a questionnaire during the months of April 2013, to April 2014. Data were analyzed through descriptive statistics. Results: 73,6% of the participants reported having sex, 58,2% always have safe sex, 50,6% use condoms in stable relationships, 89,1% use condoms with casual partners, and 44,8% did the HIV diagnostic test. Conclusion: it is necessary to invest in health education with nursing undergraduates to adopt preventive sexual behaviors against HIV.